Manual for the design of plain masonry in building structures - Seward, N. J. (Institution of Structural Engineers, 2005)
Since the publication of the first edition in 1997, a number of amendments have been made to BS5628 parts 1 and 3, the underpinning British standards to this manual. Revisions to this edition have therefore been made with reference to the current editions of these codes, BS5628-1, 2001 and BS5628-3, 2002. In view of the gradual phased introduction of BS EN (CEN) product standards for masonry and the withdrawal of the conflicting and existing British standards, this revision also includes references to both sets of standards and covers the interim period where both sets of standards apply. References to BS EN standards have been included where appropriate. -- Provided by publisher.
Previous edition: 1997.
"January 2005."
Keywords: Masonry -- Design and construction.; Structural analysis (Engineering); elektronické knihy; electronic books